Global adaptation of spring bread and durum wheat lines near-isogenic for major reduced height genes - Mathews, KL; Chapman, SC; Trethowan, R; Singh, R.P.; Crossa, J.L.; Pfeiffer, Wolfgang H.; Ginkel, M. van; DeLacy, I (Wiley, 2006)
The effect of major dwarfing genes, Rht-B1 and Rht-D1, in bread (Triticum aestivum L.) and durum (Triticum turgidum L. var. durum) wheats varies with environment. Six reduced-height near-isogenic spring wheat lines, included in the International Adaptation Trial (IAT), were grown in 81 trials around the world. Of the 56 IAT trials yielding >3 Mg ha?1, the mean yield of semidwarfs was significantly greater than talls in 54% of trials; in the 27 trials yielding <3 Mg ha?1, semidwarfs were superior in only 24%. Sixteen pairs of semidwarf–tall near-isolines were grown in six managed drought environment trials (DETs) in northwestern Mexico. In these trials, semidwarfs outyielded talls in all but the most droughted environment (2.5 Mg ha?1). The effect of the height alleles varied with genetic background and environment. For both yield and height, variance components for allele and environment by allele interaction were larger than those for genetic background and genetic background by environment. Pattern analysis showed that tall and semidwarf lines had similar adaptation to stressed environments (<2.8 Mg ha?1, low rainfall), while semidwarfs yielded more in less stressed environments (>4.3 Mg ha?1, high rainfall). The best adapted near-isogenic pair had a Kauz background, where the tall was only 16% taller than the dwarf. In the Kauz-derived pair, the semidwarf outyielded the tall in only 13% of trials with no differences in low yielding trials. This supports the idea that “short talls” may be useful in marginal environments (yield <3 Mg ha?1).